2007
DOI: 10.1111/j.1468-2397.2007.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Older family‐carers’ views on the future accommodation needs of relatives who have an intellectual disability

Abstract: Over the past 20 years, research across the developed world has identified trends towards ageing of the population with learning/intellectual disability. Alongside is the recognition that family‐carers are also ageing. Recently, the UK government has sought to identify the future housing needs of dependents with intellectual disability residing with older carers. Consequentially, a city council commissioned this qualitative study involving 28 older carers. The findings indicate a need for information about hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Within this study it was found that parents report a joint expectation for non-disabled children to develop their own independent lives yet at the same time the expectation is that they will have future involvement in the lives of the disabled person. The link found within this study between sibling involvement and parental expectation is supported within the literature by both Zetlin (1986) and Bigby (1997) and the presence of stress for parents in discussing future plans for their learning disabled off spring is also supported by studies such as those by Knox and Bigby (2007) who report that discussing futures plans with parents is a highly sensitive topic and that by Gilbert et al (2008) who found that parents were reluctant to make and discuss plans for the future.…”
Section: )Parental Influence / Impact On the Issue Of Futures Plannisupporting
confidence: 77%
“…Within this study it was found that parents report a joint expectation for non-disabled children to develop their own independent lives yet at the same time the expectation is that they will have future involvement in the lives of the disabled person. The link found within this study between sibling involvement and parental expectation is supported within the literature by both Zetlin (1986) and Bigby (1997) and the presence of stress for parents in discussing future plans for their learning disabled off spring is also supported by studies such as those by Knox and Bigby (2007) who report that discussing futures plans with parents is a highly sensitive topic and that by Gilbert et al (2008) who found that parents were reluctant to make and discuss plans for the future.…”
Section: )Parental Influence / Impact On the Issue Of Futures Plannisupporting
confidence: 77%
“…Sibling fears for the future concerned a lack of appropriate services, increased care demands and health issues. The view that futures planning is stressful for older parents and siblings is clear within existing research (Mansell & Wilson 2010;Taggart et al 2012) with main barriers cited as insufficient information and a lack of confidence in service providers (Gilbert et al 2008;Arnold et al 2012). Only three participants referred to the future wishes of the person with an intellectual disability which could suggest that they are overlooked in the futures planning process, that siblings are unaware of their wishes or are not included in the process, the literature suggests that all three scenarios are likely (Bowey & McGlaughlin 2007).…”
Section: Discussionmentioning
confidence: 99%
“…or vice versa, they may think that if they question the care they receive, this care may improve in the future. For future work, it would be advisable to complement these findings with qualitative data, as open interviews would allow the interviewee to explain the background and context and could prevent the misinterpretation of their responses (Gilbert, lankshear and petersen 2007).…”
Section: Discussionmentioning
confidence: 99%